Method for manufacturing optical elements

JP7933513B2Active Publication Date: 2026-10-13CANON KK
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2022041350
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-16
Publication Date
2026-10-13
Estimated Expiration
2042-03-16

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、短時間で膜の強度および密着性の高めることが可能な光学素子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933513000013
    Figure 0007933513000013
  • Figure 0007933513000014
    Figure 0007933513000014
  • Figure 0007933513000015
    Figure 0007933513000015
Patent Text Reader

Abstract

To provide an optical element with which it is possible to increase the strength and adhesion of a film in a short time.SOLUTION: Provided is an optical element (301) comprising a substrate (200) and an anti-reflection film (101). The anti-reflection film is composed of five or more layers including a first layer (11), a second layer (12), a third layer (13), and a fourth layer (17) that are arranged in order beginning with the one close to the substrate. The first layer is in contact with the substrate, the first and four layers are composed of a first fluorine-containing material, and the third layer is composed of a second material that is different from the first material. A tensile stress occurs to one of the first and second materials, and a compressive stress occurs to the other. The third layer is composed of a second material having a stress in the direction opposite the first material. When the thermal expansion coefficient of the substrate is assumed to be α(×10-7 / °C), the conditional expression 80<α<400 is satisfied.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to optical elements, optical systems, and optical instruments. [Background technology]

[0002] Glass materials containing fluorides such as fluorite have low dispersion properties, resulting in high chromatic aberration correction effects, and are widely used in camera lenses and other applications. However, when such glass materials are exposed to plasma containing ions or electrons, coloration called color centers occurs, preventing the acquisition of desired spectral characteristics. Patent Document 1 discloses a configuration in which the generation of color centers is prevented when depositing a film on fluorite by vapor deposition, by depositing the first layer without using ion beam-assisted deposition. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-314716 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] In the configuration disclosed in Patent Document 1, since it is necessary to increase the strength and adhesion of the film without using ion beam-assisted deposition, thermal deposition is required. In this case, heating and cooling take time to prevent rapid temperature changes.

[0005] Therefore, the present invention aims to provide an optical element that can improve the strength and adhesion of a film in a short amount of time. [Means for solving the problem]

[0006] Optical element as one aspect of the present invention Manufacturing method This is a substrate containing a fluorine compound. The process includes a step of forming an anti-reflective film by non-heating deposition.The anti-reflective film consists of five or more layers, including a first layer, a second layer, a third layer, and a fourth layer, arranged in order from the side closest to the substrate; the first layer is in contact with the substrate; the first and fourth layers are made of a first material containing fluorine; and the third layer is made of a second material different from the first material. Tensile stress is generated in the first material, The second material mentioned above includes: Compressive stress The second material comprises silicon oxide and aluminum, wherein the aluminum is 10% or less by weight of the second material, and the thermal expansion coefficient of the base material is α(×10 -7 When the refractive index is n (at / °C), the following conditions are satisfied: 80 < α < 400 and 1.43 ≤ n ≤ 1.62.

[0007] Other objects and features of the present invention are described in the following examples. [Effects of the Invention]

[0008] According to the present invention, it is possible to provide an optical element that can increase the strength and adhesion of a film in a short time. [Brief explanation of the drawing]

[0009] [Figure 1] This is a schematic cross-sectional view of the optical elements in Examples 1, 4-8. [Figure 2] This is a schematic cross-sectional view of the optical element in Example 2. [Figure 3] This is a schematic cross-sectional view of the optical element in Example 3. [Figure 4] This shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in Example 1. [Figure 5] This shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in Example 2. [Figure 6] This shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in Example 3. [Figure 7] This shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in Example 4. [Figure 8] This shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in Example 5. [Figure 9] This is the reflectance characteristic at an incident angle of 0 degrees of the optical element in Example 6. [Figure 10] This is the reflectance characteristic at an incident angle of 0 degrees of the optical element in Example 7. [Figure 11] This is the reflectance characteristic at an incident angle of 0 degrees of the optical element in Example 8. [Figure 12] This is a schematic cross-sectional view of the optical element in Example 9. [Figure 13] This is the reflectance characteristic at an incident angle of 0 degrees of the optical element in Example 9. [Figure 14] This is a schematic cross-sectional view of the optical element in Example 10. [Figure 15] This is the reflectance characteristic at an incident angle of 0 degrees of the optical element in Example 10. [Figure 16] This is a schematic cross-sectional view of the optical element in Example 11. [Figure 17] This is the reflectance characteristic at an incident angle of 0 degrees of the optical element in Example 11. [Figure 18] This is a cross-sectional view of the optical system in Example 12. [Figure 19] This is an external perspective view of the imaging apparatus in Example 13. [Modes for Carrying Out the Invention]

[0010] Hereinafter, examples of the present invention will be described in detail with reference to the drawings.

[0011] First, the schematic configuration of the optical element 301 in each example (Examples 1, 4 to 8) will be described with reference to FIG. 1. FIG. 1 is a schematic cross-sectional view of the optical element 301. The optical element 301 includes a substrate 200 and an antireflection film 101 formed over the substrate 200.

[0012] The substrate 200 is a transparent substrate made of fluorite (CaF2 crystal) or a fluorine phosphate glass material having optical constants equivalent to those of fluorite. Such glass materials have a higher fluorine compound content than other glass materials. They also have low dispersion properties and can correct chromatic aberration in optical systems. The substrate 200 is not limited to being made solely of fluorite or glass (glass material), but may be made of a material with fluorite or glass as the main component, i.e., a material with the largest proportion of fluorite or glass, and may also contain additives (impurities) other than fluorite or glass.

[0013] The thermal expansion coefficient of substrate 200 is α(×10 -7 The temperature ( / °C) satisfies, for example, the condition 80 < α < 400. Rapid temperature changes can easily cause cracking, surface changes, or crystal displacement. In each embodiment, the anti-reflective film 101 is deposited by non-heated deposition. Non-heated here means that the substrate is not actively heated using a heater or the like. During deposition, the substrate temperature may rise due to radiant heat from the deposition source, but it is acceptable as long as it is below 90°C. Furthermore, it is preferable to use ion beam assisted deposition to maintain the strength of the film. In ion beam assisted deposition with heating, color centers may occur, but in ion beam assisted deposition without heating, color centers do not occur. By using ion beam assisted deposition, the film strength and adhesion can be improved even with non-heated deposition.

[0014] The anti-reflective film 101 consists of seven layers, arranged in order from the side closest to the substrate 200: layer (first layer) 11, layer (second layer) 12, layer (third layer) 13, layers 14-16, and layer (fourth layer) 17. To achieve good anti-reflective performance, the anti-reflective film 101 must contain five or more layers. In Figure 1, the anti-reflective film 101 is shown as an example consisting of seven layers, but any number of layers, as long as it is five or more, is acceptable.

[0015] The anti-reflective film 101 includes layers made of a first material, a second material, and a third material. The first material contains a fluorine compound. Layer 11 is formed directly on the substrate 200 (placed in contact with the substrate 200) and is made of the first material. Since the substrate 200 is a glass material with a high fluorine compound content, it has high adhesion to layer 11 made of the first material containing the fluorine compound, and peeling of the film is unlikely to occur. Furthermore, it is preferable that one of the layers 12 to 17 constituting the anti-reflective film 101 (for example, layer 17) is made of the first material. The first material (material containing a fluorine compound) may be magnesium fluoride, calcium fluoride, lanthanum fluoride, neodymium fluoride, or cerium fluoride. In each embodiment, magnesium fluoride is more preferable from the viewpoint of low refractive index and ease of deposition. Generally, it is preferable that the outermost layer of the anti-reflective film is made of a material with a low refractive index. This is because a low refractive index in the outermost layer of the anti-reflective film reduces the reflectivity. Therefore, it is preferable that the layer 17 of the anti-reflective film 101, which is the layer furthest from the substrate 200 (outermost layer), be made of the first material.

[0016] The refractive index n1 at the d line of the layers made of the first material (for example, layers 11 and 17) preferably satisfies the following condition (1).

[0017] 1.30 ≤ n1 ≤ 1.40 …(1) Tensile stress occurs in the layers made of the first material, which is a material containing a fluorine compound (for example, layers 11 and 17). In particular, strong tensile stress occurs in the layer made of magnesium fluoride. In order to relieve the stress on the entire anti-reflective film 101, it is necessary to have a layer in which compressive stress occurs, which is a stress opposite to the tensile stress. For this reason, it is preferable that compressive stress occurs in the layers made of a second material different from the first material (for example, layers 13 and 15), which is a stress in the opposite direction to that of the first material.

[0018] The second material is preferably a material containing silicon oxide. The silicon oxide vapor-deposited film has compressive stress. To have stronger compressive stress, it is preferable to include a small amount of aluminum. Furthermore, it is preferable that the amount of aluminum included is 10% or less by weight of the second material. In addition, it is preferable that the refractive index n2 at the d line of the layers made of the second material (for example, layers 13 and 15) satisfies the following condition (2).

[0019] 1.40 ≤ n² ≤ 1.50 …(2) The amount of aluminum in the second material can be very small, and by satisfying condition (2), the layer made of the second material has strong compressive stress. The anti-reflective coating 101 has layers 13 and 15 as layers made of the second material.

[0020] In the anti-reflective film 101, the physical film thickness d1 (nm) of layer 11 preferably satisfies the following condition (3).

[0021] 10 ≤ d1 ≤ 90 …(3) A physical film thickness d1 smaller than 10 nm is undesirable because it makes it difficult to adjust the film thickness during deposition. On the other hand, a physical film thickness d1 larger than 90 nm is also undesirable because the tensile stress increases, and the compressive stress of layers 13 and 15 makes it difficult to relieve the stress on the entire film.

[0022] Next, the schematic configurations of the optical elements 302 and 303 in Examples 2 and 3 will be described with reference to Figures 2 and 3. Figure 2 is a schematic cross-sectional view of the optical element 302 in Example 2. Figure 3 is a schematic cross-sectional view of the optical element 303 in Example 3. The optical elements 302 and 303 each have a substrate (base material) 200 and anti-reflective films 102 and 103 formed on the substrate 200, respectively.

[0023] As shown in Figure 2, the anti-reflective coating 102 consists of eight layers, layers 11 to 18. In the anti-reflective coating 102, layers 1 to 17 have the same configuration as the anti-reflective coating 101, and layer 18 is provided on layer 17. That is, layer 18 is the fifth layer, further from the substrate 200 than layer 17. As shown in Figure 3, the anti-reflective coating 103 consists of nine layers, layers 11 to 19. In the anti-reflective coating 103, layers 1 to 18 have the same configuration as the anti-reflective coating 102, and layer 19 is provided on layer 18. That is, layer 19 is the sixth layer, the furthest from the substrate 200. In the anti-reflective coatings 102 and 103, layer 17 consists of a first material containing a fluorine compound similar to that of layer 11, and layer 18 consists of a second material. In the anti-reflective coating 103, layer 19 consists of a fourth material containing a fluorine-containing organic compound that has water-repellent and anti-fouling effects. In optical element 302, layer 18, which is the outermost layer (farthest from the substrate 200), is made of a second material containing silicon dioxide, and therefore has greater film strength. In optical element 303, layer 19, which is the outermost layer (farthest from the substrate 200), is made of a fourth material with high water-repellent and anti-fouling properties, and therefore has water-repellent and anti-fouling functions.

[0024] In the anti-reflective films 101, 102, and 103 of each embodiment, layers 12, 14, and 16 are each made of a third material. The refractive index n3 at the d line of layers 12, 14, and 16 made of the third material preferably satisfies the following condition (4).

[0025] 1.90 ≤ n3 ≤ 2.40 …(4) The third material is different from the first and second materials. In each example, the third material is tantalum oxide, titanium oxide, lanthanum oxide, or zirconium oxide. Hmm It is preferable that the material is primarily composed of one of these, or a mixture of these.

[0026] In the anti-reflective films 101, 102, and 103, the layer closest to the substrate 200 (the first layer) is made of a first material, and the subsequent layers consist of alternating layers of a third material and a second material. A layer 17 made of the first material is formed on top of a layer 16 made of the third material.

[0027] The following describes each embodiment in detail. [Examples]

[0028] Figure 1 is a schematic cross-sectional view of the optical element 301 in Example 1. The optical element 301 in this example is an optical element in which an anti-reflective film 101 is formed on a substrate 200. The substrate 200 is made of fluorite (refractive index: 1.43 (d line), coefficient of thermal expansion (-30℃~70℃): 240 × 10 -7 The temperature is ( / °C). The layer materials used are SiO2 (Al weight ratio 4.5%), MgF2, and Ta2O5. Table 1 shows the details of the film structure of the optical element in this embodiment.

[0029] The method for forming the anti-reflective film 101 in this embodiment is as follows. The anti-reflective film 101 is formed by vapor deposition. An electron beam is used to heat the evaporation material. In addition, an ion beam-assisted vapor deposition method is employed to form a denser film. The vacuum chamber inside the vapor deposition apparatus is 2 × 10 -3 The chamber is evacuated without heating to a high vacuum region near (Pa). After confirming that the vacuum chamber has reached a high vacuum state, Ar is introduced into the ion gun as an inert gas, and the ion gun is discharged. Once the ion gun has stabilized, oxygen is introduced into the vacuum chamber, and the vacuum pressure is 1 × 10⁻⁶. -2 Ion-assisted deposition using oxygen ions is performed at approximately (Pa) pressure.

[0030] Figure 4 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. In Figure 4, the horizontal axis represents wavelength (nm), and the vertical axis represents reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.2% or less, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0031] To confirm the durability of the anti-reflective coating 101 under various conditions, the following durability tests were conducted. (High temperature and high humidity storage test) The prepared samples were left in a constant temperature chamber set to 60°C and 90% humidity for 1000 hours, after which the appearance of the anti-reflective coating was visually observed. (Low-temperature storage test) The prepared samples were left in a constant temperature bath set to -30°C for 1000 hours, and then the appearance of the anti-reflective coating was visually observed. (High-temperature storage test) The prepared samples were left in a constant temperature bath set to 70°C for 12 hours, and then the appearance of the anti-reflective coating was visually observed. (Adhesion test) After attaching adhesive tape to the surface of the anti-reflective coating of the prepared sample, the tape was peeled off perpendicular to the coating surface. This process was repeated five times, and the film was visually inspected to see if it had peeled off. (Surface hardness test) After applying a load of approximately 200g to a piece of lens tissue coated with solvent and rubbing the anti-reflective coating back and forth 10 times, the appearance of the anti-reflective coating was visually observed.

[0032] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0033] [Table 1] [Examples]

[0034] Figure 2 is a schematic cross-sectional view of the optical element 302 in Example 2. The optical element 302 in this example is an optical element in which an anti-reflective film 102 is formed on a substrate 200. The substrate 200 is made of fluorite (refractive index: 1.43 (d line), thermal expansion coefficient (-30℃~70℃): 240 × 10⁻¹⁴). -7The temperature is ( / °C). SiO2 (Al weight ratio 4.5%), MgF2, and Ta2O5 are used as the layer materials. Table 2 shows the details of the film structure of the optical element in this example. The film deposition conditions are the same as those in Example 1.

[0035] Figure 5 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.25% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0036] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0037] [Table 2] [Examples]

[0038] Figure 3 is a schematic cross-sectional view of the optical element 303 in Example 3. The optical element 303 in this example is an optical element in which an anti-reflective film 103 is formed on a substrate 200. The substrate 200 is made of fluorite (refractive index: 1.43 (d line), coefficient of thermal expansion (-30℃~70℃): 240 × 10 -7 The temperature is ( / °C). The layer materials used are SiO2 (Al weight ratio 4.5%), MgF2, and Ta2O5. OF-SR (manufactured by Canon Optron Co., Ltd.) is used as the fluorine-containing organic compound. Table 3 shows the details of the film structure of the optical element in this example. The film deposition conditions for layers 11 to 18 are the same as those in Example 1. Layer 19 is deposited at a film deposition temperature of 80°C using resistance heating deposition. After film deposition is complete, excess OF-SR is removed by wiping the surface of the removed optical element 303 with ethanol.

[0039] Figure 6 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.25% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0040] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0041] [Table 3] [Examples]

[0042] The optical element 301 of Example 4 is an optical element in which an anti-reflective film 101 is formed on a substrate 200, similar to Figure 1. The substrate 200 is S-FPL51 (manufactured by OHARA Corporation, refractive index: 1.50 (d line), thermal expansion coefficient (-30℃~70℃): 131 × 10⁻¹⁰ -7 The temperature is ( / °C). The layer materials used are SiO2 (Al weight ratio 1.0%), MgF2, and a mixture of Ta2O5 and TiO2. Table 4 shows the details of the film structure of the optical element in this example. The film deposition conditions are the same as those in Example 1. Layers 11 and 17, made of MgF2, are deposited by resistance heating deposition and ion-assisted beam deposition.

[0043] Figure 7 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.2% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0044] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0045] [Table 4]

Examples

[0046] The optical element 301 of Example 5 is an optical element in which an antireflective film 101 is formed on a substrate 200, similarly to FIG. 1. The substrate 200 is S-FPL53 (manufactured by OHARA Inc., refractive index: 1.44 (d-line), thermal expansion coefficient (-30°C to 70°C): 169×10 -7 / °C). As the materials of the layers, SiO₂ (Al weight ratio 1.0%), MgF₂, and a mixture of Zr₂O₅ and TiO₂ are used. Table 5 shows the details of the film configuration of the optical element of this example. The film formation conditions are the same as those of Example 1.

[0047] FIG. 8 shows the reflectance characteristics at an incident angle of 0 degrees of the optical element in this example. In the wavelength range of 420 to 680 nm, the reflectance is 0.2% or less, which is a very favorable characteristic. It can also be visually confirmed that no color centers are generated.

[0048] The results of the durability test are shown in Table 12. In all tests, no film cracking or film peeling occurred, and it can be confirmed that a favorable antireflective film is formed.

[0049]

Table 5

Examples

[0050] The optical element 301 of Example 6 is an optical element in which an antireflective film 101 is formed on a substrate 200, similarly to FIG. 1. The substrate 200 is S-FPM2 (manufactured by OHARA Inc., refractive index: 1.60 (d-line), thermal expansion coefficient (-30°C to 70°C): 135×10 -7 / °C). As the materials of the layers, SiO₂ (Al weight ratio 1.0%), MgF₂, and a mixture of Ta₂O₅ and TiO₂ are used. Table 6 shows the details of the film configuration of the optical element of this example. The film formation conditions are the same as those of Example 1.

[0051] Figure 9 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.2% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0052] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0053] [Table 6] [Examples]

[0054] The optical element 301 of Example 7 is an optical element in which an anti-reflective film 101 is formed on a substrate 200, similar to Figure 1. The substrate 200 is S-FTM16 (manufactured by OHARA Corporation, refractive index: 1.60 (d line), thermal expansion coefficient (-30℃~70℃): 100×10 -7 The temperature is ( / °C). The layer material used is a mixture of SiO2 (8.0% Al by weight), MgF2, Zr2O5, and TiO2. Table 7 shows the details of the film structure of the optical element in this example. The film deposition conditions are the same as those in Example 4.

[0055] Figure 10 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.2% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0056] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0057] [Table 7] [Examples]

[0058] The optical element 301 of Example 8 is an optical element in which an anti-reflective film 101 is formed on a substrate 200, similar to Figure 1. The substrate 200 is S-PHM52 (manufactured by OHARA Corporation, refractive index: 1.62 (d line), thermal expansion coefficient (-30℃~70℃): 101 × 10⁻¹⁰ -7 The temperature is ( / °C). SiO2 (8.0% Al by weight), MgF2, and Ta2O5 are used as the layer materials. Table 8 shows the details of the film structure of the optical element in this example. The film deposition conditions are the same as those in Example 4.

[0059] Figure 11 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.2% or less in the wavelength range of 420 to 680 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0060] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0061] [Table 8] [Examples]

[0062] Figure 12 is a schematic cross-sectional view of the optical element 301-2 in Example 9. The optical element 301-2 in this example is an optical element in which an anti-reflective film 101-2 is formed on a substrate 200. The substrate 200 is S-FPL51 (manufactured by OHARA Corporation, refractive index: 1.60 (d line), thermal expansion coefficient (-30℃~70℃): 131 × 10 -7 The temperature is ( / °C). The layer material used is a mixture of SiO2 (Al weight ratio 4.5%), MgF2, Ta2O5, and TiO2. Table 9 shows the details of the film structure of the optical element in this example. The film deposition conditions are the same as those in Example 1.

[0063] Figure 13 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.5% or less in the wavelength range of 420 to 900 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0064] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0065] [Table 9] [Examples]

[0066] Figure 14 is a schematic cross-sectional view of the optical element 302-2 in Example 10. The optical element 302-2 in this example is an optical element in which an anti-reflective film 102-2 is formed on a substrate 200. The substrate 200 is S-PHM52 (manufactured by OHARA Corporation, refractive index: 1.62 (d line), thermal expansion coefficient (-30℃~70℃): 10¹×10¹⁴ -7 The temperature is ( / °C). The layer material used is a mixture of SiO2 (Al weight ratio 4.5%), MgF2, Ta2O5, and TiO2. Table 10 shows the details of the film structure of the optical element in this example. The film deposition conditions are the same as those in Example 2.

[0067] Figure 15 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.5% or less in the wavelength range of 420 to 880 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0068] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0069] [Table 10] [Examples]

[0070] Figure 16 is a schematic cross-sectional view of the optical element 303-2 in Example 11. The optical element 303-2 in this example is an optical element in which an anti-reflective film 103-2 is formed on a substrate 200. The substrate 200 is S-FPM2 (manufactured by OHARA Corporation, refractive index: 1.60 (d line), thermal expansion coefficient (-30℃~70℃): 136 × 10 -7 The temperature is ( / °C). The layer material used is a mixture of SiO2 (Al weight ratio 4.5%), MgF2, Ta2O5, and TiO2. Table 11 shows the details of the film structure of the optical element in this example. The film deposition conditions are the same as those in Example 3.

[0071] Figure 17 shows the reflectance characteristics of the optical element at an incident angle of 0 degrees in this embodiment. The reflectance is 0.5% or less in the wavelength range of 420 to 880 nm, which is a very good characteristic. Furthermore, the absence of color centers can be visually confirmed.

[0072] The results of the durability tests are shown in Table 12. In all tests, no cracking or peeling of the film occurred, confirming that a good anti-reflective coating was formed.

[0073] [Table 11]

[0074] [Table 12] [Examples]

[0075] Next, the optical system in Example 12 will be described with reference to Figure 18. Figure 18 is a cross-sectional view of the optical system 401. The optical system 401 has a plurality of optical elements G401 to G416. 402 is the aperture, and 403 is the image plane. Optical elements G401 to G411 are lenses. Of these optical elements, optical elements G403, G412, and G413 are made of a glass material having low dispersion, and an anti-reflective coating of any of Examples 1 to 11 is provided on at least one of the incident surface and the exit surface. That is, the optical system 401 has a plurality of optical elements G401 to G411, and the plurality of optical elements G403, G412, and G413 include optical elements on which an anti-reflective coating of any of Examples 1 to 11 is formed.

[0076] Furthermore, the optical system 400 in this embodiment is not limited to the imaging optical system used in the imaging device described later, but can also be applied to optical systems for various applications such as binoculars, projectors, and telescopes. [Examples]

[0077] Next, the imaging device in Example 13 will be described with reference to Figure 19. Figure 19 is an external perspective view of the imaging device (digital camera 500).

[0078] The digital camera 500 has a camera body 502 and a lens device 501 which is integrally configured with the camera body 502. However, this embodiment is not limited to this, and the lens device 501 may be an interchangeable lens that can be attached to and removed from the camera body 502, such as for an SLR camera or a mirrorless camera. In this case, Figure 19 corresponds to the state in which the lens device 501 is attached to the camera body 502. The lens device 501 has the optical system 401 of Embodiment 12. The camera body 502 has an image sensor 503 such as a CMOS sensor or a CCD sensor. The image sensor 503 is positioned on the imaging plane 403 of the optical system 401.

[0079] According to each embodiment, it is possible to provide optical elements, optical systems, and optical instruments that can improve the strength and adhesion of the film in a short time.

[0080] Although preferred embodiments of the present invention have been described above, the present invention is not limited to these embodiments, and various modifications and changes are possible within the scope of its essence.

[0081] For example, in each embodiment, tensile stress is generated in the first material and compressive stress is generated in the second material, but this is not limited to this. It is sufficient that tensile stress is generated in one of the first and second materials and compressive stress is generated in the other. [Explanation of symbols]

[0082] 101, 102, 103 Anti-reflection coating 11th layer (1st layer) 12th layer (2nd layer) 13th layer (3rd layer) 17th layer (4th layer) 200 substrates (base materials) 301, 302, 303 Optical elements

Claims

1. The process involves forming an anti-reflective film on a substrate containing a fluorine compound by non-heating vapor deposition. The anti-reflective coating consists of five or more layers, including a first layer, a second layer, a third layer, and a fourth layer, arranged in order from the side closest to the substrate. The first layer is in contact with the substrate, The first layer and the fourth layer are made of a first material containing fluorine. The third layer is made of a second material different from the first material. Tensile stress is generated in the first material, Compressive stress is generated in the second material. The second material comprises silicon dioxide and aluminum, The aluminum is 10% or less by weight of the second material. The thermal expansion coefficient of the substrate is α(×10) -7 When the refractive index is n (in degrees Celsius), 80<α<400 1.43 ≤ n ≤ 1.62 A method for manufacturing an optical element, characterized by satisfying the following conditional equation.

2. The method for manufacturing an optical element according to claim 1, characterized in that the first material contains magnesium fluoride.

3. The physical thickness of the first layer is d 1 When (nm), 10≦d 1 ≦90 A method for manufacturing an optical element according to claim 1 or 2, characterized in that it satisfies the following conditional expression.

4. The refractive index of the first layer made of the first material at line d is n 1 In that case, 1.30≦n 1 ≦1.40 A method for manufacturing an optical element according to any one of claims 1 to 3, characterized in that it satisfies the following conditional expression.

5. The refractive index of the third layer made of the second material at line d is n 2 In that case, 1.40≦n 2 ≦1.50 A method for manufacturing an optical element according to any one of claims 1 to 3, characterized in that it satisfies the following conditional expression.

6. The method for manufacturing an optical element according to any one of claims 1 to 5, characterized in that the fourth layer is the layer of the anti-reflective film furthest from the substrate.

7. The anti-reflective film has a fifth layer that is furthest from the substrate, The method for manufacturing an optical element according to any one of claims 1 to 5, characterized in that the fifth layer is made of the second material.

8. The anti-reflective film has a sixth layer that is furthest from the substrate, The method for manufacturing an optical element according to claims 1 to 5, characterized in that the sixth layer contains a fluorine-containing organic compound and is provided on a fifth layer made of the second material.

9. The method for manufacturing an optical element according to any one of claims 1 to 8, characterized in that the second layer is made of a third material different from the first material and the second material.

10. The refractive index of the second layer made of the third material at line d is n 3 In that case, 1.90≦n 3 ≦2.40 A method for manufacturing an optical element according to claim 9, characterized in that it satisfies the following conditions.

11. The method for manufacturing an optical element according to claim 9 or 10, characterized in that the third material is a material mainly composed of one of tantalum oxide, titanium oxide, lanthanum oxide, or zirconium oxide, or a mixture thereof.

Citation Information

Patent Citations

  • Optical imaging lens

    CN215297782U

  • Optical component

    JP1993002101A

  • Optical part, manufacture thereof, and manufacturing apparatus

    JP1997314716A

  • Antireflection film and optical parts

    JP2002267803A

  • Antireflection film and optical element

    JP2003021702A